Desain Aplikasi Edukasi Berbasis Mobile Tentang Asi Eksklusif Dalam Upaya Pencegahan Stunting Menggunakan Rapid Application Development - Febriyani, Anisa; Ramdani, Mohamad Faiz; Saputra, Ragil Yudi; Asih, Wina Tri; Jayusman, Hadi (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat 2025, 2025)
This study aims to design and develop a mobile-based educational application on the importance of exclusive breastfeeding in preventing stunting using the Rapid Application Development (RAD) method. Stunting remains a significant health issue in Indonesia, and the lack of awareness regarding the benefits of exclusive breastfeeding contributes to its prevalence. The application was developed to provide an accessible and interactive educational tool for mothers and caregivers. The RAD methodology was chosen for its rapid and iterative approach, which includes requirement planning, user design, rapid construction, and transition phases. The application presents comprehensive information on exclusive breastfeeding, its benefits for infant health, and its role in stunting prevention. In addition, the application focuses on providing practical features such as breastfeeding schedule reminders, breastfeeding care tips, breastfeeding activity recording, and engaging multimedia content to enhance user understanding and involvement. User testing results indicated a high level of satisfaction with the usability and effectiveness of the application, as users felt supported in obtaining information and maintaining consistency in exclusive breastfeeding practices. Implementation challenges, including technical issues and user adoption, were successfully identified and addressed during the development process. Therefore, this application is expected to serve as an innovative, interactive, and beneficial educational tool to increase public awareness of the importance of exclusive breastfeeding as an effort to prevent stunting in Indonesia.